Imaging and Simulation Techniques for Lower Limb Deformity: A Literature Review (Iraqi Journal of Medical Sciences, 2025)
Malalignment syndrome involves improper anatomical positioning due to musculoskeletal abnormalities, often resulting in torsional deformities that impair function and require surgical intervention. Traditional surgical planning methods have limitations in precision and consistency. This review aimed to explore recent advances in computer-aided surgical simulation and digital 3D skeletal modeling techniques used to assess and correct lower limb deformities. It was conducted to analyze current methods in 3D surgical planning, focusing on computer-aided simulations and the use of personalized surgical guides. Sources were selected from peer-reviewed journals and databases, evaluating their applications in clinical practice. Studies showed that computer-assisted surgical simulation enhances preoperative planning, improves alignment accuracy, reduces intraoperative complexity, and decreases surgery time. Personalized guides developed from digital modeling have demonstrated improved outcomes and reduced surgical trauma. Computer-aided 3D modeling and personalized surgical planning represent significant advancements in deformity correction. These tools provide surgeons with improved visualization, simulation capabilities, and efficiency, ultimately supporting safer and more accurate surgical interventions. Keywords: Computer-aided surgical simulation, surgical planning, 3D motion analysisCitation: Akar BA, Ghazwan AG, Al-Saadan WA. Imaging and simulation techniques for lower limb deformity: A literature review. Iraqi JMS. 2025; 23(1): 1-16. doi: 10.22578/IJMS.23.1.1